Mechanisms of vascularization in murine models of primary and metastatic tumor growth. Issue 1 (December 2016) - Bugyik, Edina; Renyi-Vamos, Ferenc; Szabo, Vanessza; Dezso, Katalin; Ecker, Nora; Rokusz, Andras; Nagy, Peter; Dome, Balazs; Paku, Sandor
Abstract Directed capillary ingrowth has long been considered synonymous with tumor vascularization. However, the vasculature of primary tumors and metastases is not necessarily formed by endothelial cell sprouting; instead, malignant tumors can acquire blood vessels via alternative vascularization mechanisms, such as intussusceptive microvascular growth, vessel co-option, and glomeruloid angiogenesis. Importantly, in response to anti-angiogenic therapies, malignant tumors can switch from one vascularization mechanism to another. In this article, we briefly review the biological features of these mechanisms and discuss on their significance in medical oncology.